Synthesis and dielectric and ferroelectric properties of ceramics in (1 - X)Pb(Zr1/2Ti1/2)O3-(x)Pb(Co 1/3Nb2/3)O3 system - Prasatkhetragarn, Anurak; Vittayakorn, Naratip; Ananta, Supon; Yimnirun, Rattikorn; Cann, David P. (My University, 2008)
Ceramics in a PZT-PCN system with the formula (1 - x)Pb(Zr 1/2Ti1/2)O3-(x)Pb(Co1/3Nb 2/3)O3, where x = 0.1-0.5, were prepared using a solid-state mixed-oxide technique (the columbite-wolframite precursor method). The phase formation behavior and microstructure were studied using X-ray diffraction (XRD) analysis and scanning electron microscopy (SEM), respectively. The dielectric and ferroelectric properties of the compounds were studied and discussed. Phase-pure perovskites of PZT-PCN ceramics were obtained over a wide compositional range. In addition, the XRD, dielectric, and ferroelectric properties confirmed that the morphotropic phase boundary (MPB) composition between the tetragonal and pseudo cubic phases of this system lied between 0.2 ≤ × ≤ 0.3. © 2008 The Japan Society of Applied Physics.
Keywords: Ferroelectric properties; MPB; Perovskites; Phase transition